2022
DOI: 10.2478/fhort-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of potassium silicate, potassium fulvate and betaine improve summer-time tomato yield by promoting plant nitrogen and potassium uptake

Abstract: During the summer months, greenhouse tomato production is challenged by the heat, causing yield reduction; therefore, we conducted a study to test the effectiveness of different foliar spray compositions for the improvement of Lycopersicon esculentum var. cerasiforme ‘Qianxi’ nutrition uptake and fruit yield. Two forms of silicon, two kinds of organic nitrogenous compounds and water as the control factor were two-two paired to become nine different recipes, which were as follows: CK (H2O), ISi (K2SiO3), organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Under other stress conditions, such as salinity, a decrease in antioxidant activity, and H 2 O 2 , MDA, and proline contents was observed in cherry tomato plants after the application of humic-based substances as seed coatings or drench solutions [63]. On the other hand, humic substances also have beneficial properties under non-stress conditions; for example, foliar applications of potassium fulvate in greenhouse tomatoes stimulated potassium and nitrogen uptake with increased yields [64].…”
Section: Discussionmentioning
confidence: 99%
“…Under other stress conditions, such as salinity, a decrease in antioxidant activity, and H 2 O 2 , MDA, and proline contents was observed in cherry tomato plants after the application of humic-based substances as seed coatings or drench solutions [63]. On the other hand, humic substances also have beneficial properties under non-stress conditions; for example, foliar applications of potassium fulvate in greenhouse tomatoes stimulated potassium and nitrogen uptake with increased yields [64].…”
Section: Discussionmentioning
confidence: 99%
“…32 In the research conducted by Xiangnan Xu and colleagues, they compared nine formulas and found that potassium silicate combined with potassium humic acid and potassium silicate alone promoted plant nitrogen absorption, increasing by 8.2% and 18.8%, as well as potassium absorption, which was 16.2% and 12.3% compared to CK, respectively. 33 Simultaneously, research has indicated that the use of nano molybdenum has positive effects on the nitrogen utilization efficiency and yield in green beans. Nano molybdenum chelates and sodium molybdate increased the biomass of mung beans by 24.31% and 36.47%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, its specific relationship with nitrogen uptake remains uncertain. On the other hand, Xu et al (2022) reported that foliar spray with potassium fulvate (0.5 g dm −3 ) resulted in a significant improvement in fruit yield, with a 17% better performance compared to the control group (CK) that received only water (H2O). Foliar spraying with a mixture of potassium silicate and fulvic acid increased the leaf content of chlorophyll a, carotene, and TSS, while foliar spraying with potassium silicate only increased the leaf content of chlorophyll b.…”
Section: Discussionmentioning
confidence: 99%